2022
DOI: 10.1038/s41467-022-29818-z
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous oyster fisheries persisted for millennia and should inform future management

Abstract: Historical ecology has revolutionized our understanding of fisheries and cultural landscapes, demonstrating the value of historical data for evaluating the past, present, and future of Earth’s ecosystems. Despite several important studies, Indigenous fisheries generally receive less attention from scholars and managers than the 17th–20th century capitalist commercial fisheries that decimated many keystone species, including oysters. We investigate Indigenous oyster harvest through time in North America and Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 73 publications
1
38
0
1
Order By: Relevance
“…Preprints make early versions of non peer-reviewed articles permanently available and citable, until they become peer-reviewed. The great interest in oysters we identified here could be due to the fact that oysters play vital roles in ecosystems and are commercially harvested organisms with great economic importance, (Dumbauld et al, 2009;Fleury et al, 2009;Reeder-Myers et al, 2022;Smith et al, 2022). The present study also found that 80% of the retrieved articles are considered open access, strongly supporting the growing interest of science as a whole towards making research openly accessible.…”
Section: Discussion Oyster's Global Publication Trendssupporting
confidence: 71%
“…Preprints make early versions of non peer-reviewed articles permanently available and citable, until they become peer-reviewed. The great interest in oysters we identified here could be due to the fact that oysters play vital roles in ecosystems and are commercially harvested organisms with great economic importance, (Dumbauld et al, 2009;Fleury et al, 2009;Reeder-Myers et al, 2022;Smith et al, 2022). The present study also found that 80% of the retrieved articles are considered open access, strongly supporting the growing interest of science as a whole towards making research openly accessible.…”
Section: Discussion Oyster's Global Publication Trendssupporting
confidence: 71%
“…This could shed light on the biomass represented in sites as well as the intensity of site use over time with implications for the modern use of marine resources (cf. Duffield et al 2022; Reeder-Myers et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Under the pressing global change situation, historical information can be critical to understand the magnitude and rhythms of ecosystem change (Reeder‐Myers et al, 2022; Zu Ermgassen et al, 2012), to identify the role of different human activities driving them (Thurstan, 2022) and to define meaningful reference scenarios for biodiversity recovery (Collins et al, 2020). This long‐term knowledge is needed to better adapt to and, when possible, mitigate the impacts of different global change components.…”
Section: Archival Sources For Biodiversity Knowledgementioning
confidence: 99%